ANALYSIS OF INCLUSIVE EDUCATION LEARNING MANAGEMENT FOR CHILDREN WITH SPECIAL NEEDS (ABK) AT STATE MIDDLE SCHOOL 1 PALU - Lily Septiani; Sagaf S Pettalongi; Muhammad Djamil M (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2026)
Inclusive education is a strategic instrument to guarantee equal educational rights for Children with Special Needs (ABK). SMP Negeri 1 Palu as a public educational institution has committed to providing inclusive services, but its effectiveness is highly dependent on the implemented learning management governance. This study aims to analyze the learning management of inclusive education at SMP Negeri 1 Palu, especially in the planning and organizing aspects for students with diverse characteristics. This study uses a descriptive qualitative approach. Data were collected through direct observation, in-depth interviews with the principal, vice principal for curriculum, and subject teachers, and documentation. Method triangulation techniques were used to ensure the validity of the data. The research findings indicate that: (1) Learning planning begins with a scientific identification mechanism through the affirmative PPDB pathway (15% quota) and the implementation of an adaptive curriculum with a simplified Learning Implementation Plan (RPP); (2) Prominent instructional strategies include peer tutoring methods and role differentiation to build students' psycho-social aspects; (3) Organization is carried out through active collaboration between teachers and communication with parents to overcome systemic limitations. Inclusive learning management at SMP Negeri 1 Palu has been implemented creatively at the instructional level, but faces challenges related to human resources and infrastructure. The absence of a permanent Special Guidance Teacher (GPK) and the unavailability of specific learning media have resulted in the burden of curriculum adaptation falling entirely on regular teachers. Policy interventions are needed to procure expert staff and optimize physical facilities to support the sustainability of the inclusive program